The real McCoy and other ghost stories - Thompson, Lesley (Oxford : Oxford University Press, 2010)
Dominoes is a full-colour, interactive readers series that offers students a fun reading experience while building their language skills. With integrated activities and on-page glossaries the new edition of the series makes reading motivating for learners. Each reader is carefully graded to ensure each student reads from the right level from the very beginning.
'Are you scared, Gordon?' asks Heather. Four friends talk of ghosts in a hotel in Scotland. That night Gordon sees and hears something strange in his room. But is it really the ghost of Lord McCoy? These six stories tell of ghosts - friendly, sad, and bad - from Britain, Australia, New Zealand, America - and Egypt!
Level 1.
Keywords: Readers (Adult); English language -- Textbooks for foreign speakers; Stage books